The Law of the Seabed Access, Uses, and Protection of Seabed Resources - Banet, Catherine (Publications on Ocean Development, 2020)
The Law of the Seabed offers a timely analysis of the most pressing legal questions raised by the use and protection of natural resources on and underneath the world's seabeds. Readership: University students, lecturers, academics/researchers, governments, law-makers, negotiators, international organisations, NGOs, lobby organisations, practitioners, commercial and in-house lawyers.